Penyuluhan Kesehatan tentang Kanker Serviks pada Wanita Usia Subur (WUS) di Desa Kertawinangun Kecamatan Kedawung Kabupaten Cirebon - Sofiyati Sofiyati; Marwati Marwati (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
Cervical cancer is a primary malignant tumor originating from squamous epithelial cells or cells originating from the vagina and urethra, usually occurring in the cervix or cervix which is located between the uterus and the sexual canal (vagina). According to WHO 2018, cervical cancer is the fourth leading cause of death in women throughout the world, estimated at 570,000, while new cases in 2018 or 6.6% of all cancers in women. Human papilloma virus or commonly called (HPV) is known to cause cervical cancer which can be transmitted through sexual intercourse, infection with several types of viruses, and personal hygiene. Symptoms of cervical cancer can be recognized by the presence of fluid from the birth canal, namely abnormal vaginal discharge, contact bleeding (bleeding during intercourse), and feeling pain during coitus / sexual intercourse as well as bleeding even after entering menopause. Early symptoms of pre-cancerous conditions are generally characterized by the discovery of abnormal cells. These abnormal cells develop into cervical cancer and then the following symptoms of cervical cancer appear; the appearance of pain and bleeding during sexual intercourse (contact bleeding), abnormal vaginal bleeding, such as bleeding outside the menstrual cycle, bleeding between regular menstrual periods, menstrual periods that are longer and more abundant than usual, bleeding after menopause, vaginal discharge excessive and abnormal, if the cancer has spread to the pelvis, the patient will suffer from complaints of pelvic pain, difficulty urinating, and enlarged kidneys. Cervical cancer can be prevented 100% by HPV vaccination, using condoms, avoiding tobacco consumption, and early detection and treatment of precancerous lesions.